A longitudinal approach to assessing vulnerability to climate change in Ulukhaktok, NT, Canada - Fawcett, David; Pearce, T; Ford, J; Notaina, R (ArcticNet Inc., 2016)
Climate change is already affecting Arctic ecosystems and the human communities that rely on them for their livelihoods, and these changes are expected to continue in the future necessitating human adaptation in response. Adaptation research conducted in 2005 in Ulukhaktok, NT identified particular vulnerabilities in the Inuit subsistence hunting sector and Inuit responses to these changes. These findings made significant contributions to our understanding of the human dimensions of climate change in the Arctic, but are temporally discrete, providing a static understanding of vulnerability and adaptation, which are dynamic processes. In response, this research examined the processes and dynamism of climate change vulnerability in Ulukhaktok through a longitudinal study, using fieldwork data from both 2005 and 2016 alongside historical data, and longitudinal instrumental, economic, and harvest data. Specific objectives included: (1) document current exposure-sensitivities affecting Inuit subsistence hunting and the adaptive strategies employed to manage them; (2) compare current exposure-sensitivities and responses with those documented in 2005 (Pearce et al. 2010); and (3) describe the processes and conditions which have aided or constrained adaptation over time. Data was collected through semi-structured interviews (n=32), participant observation, and closely working with an active Inuit hunter as a research partner. Among several themes, the data indicates that many of the changes recorded in 2005 have continued, with changes to wind, ice, and snow conditions being of particular relevance and altering the timing and ability of people to go hunting or the success of hunting. Furthermore, the significant role of specific economic, social, and political changes and conditions in determining individual sensitivity and responses to certain conditions was uncovered in greater detail. This research contributes a dynamic understanding of community vulnerability and adaptation in Ulukhaktok, an understanding of the dynamic processes of vulnerability and adaptation including how climatic and non-climatic variables interact and converge, and to the methodological advancement of the Vulnerability Approach through the operationalization of a longitudinal design. This research is part of ArcticNet Project 1.1 Community Vulnerability, Adaptation and Resilience to Climate Change in the Arctic.